Ensino da língua portuguesa para surdos: contornos de práticas bilíngues - Dias Júnior, Jurandir Ferreira (2010)
This dissertation is the result of research developed during the course Master of Language Sciences, at the line of research on language acquisition and development, to the degree of master. The aim of this study is to analyze the strategies and methods employed by Portuguese teachers to deaf students studying in primary and high schools in Recife that offer bilingual classrooms, checking the suitability for desired educational objectives. At this research, ten (10) teachers participated. They was 05 (five) from the private school and 05 (five) from the public school. We set up our corpus with questionnaire, interview and lesson observation forms. The theory was based on the work of Krashen (1984, 1995), Selinker (1972, 1978, 1994), Quadros (1997, 2006, 2009) and Brochado (2003), among others. Whereas the Portuguese language for the deaf is a second language (L2), the teaching of this language should be realized as such. However, it was not what we find in so-called bilingual classrooms, where the deaf person is present as a mere spectator of an event which does not participate. We realized, though, the need for adapting strategies and methods chosen by teachers for classroom time, in view of the specificities required for deaf students, the model inclusivist.